Effect of heating time and temperature to the dielectric properties of pork and chicken in the range of 0.5 – 50 GHz - Zainal Abidin, Zurina; Omar, Fatin Nordalila; Awang Biak, Dayang Radiah (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2017)
The interaction of materials with electromagnetic energy in microwave range provides dielectric constant (ε′) and loss (ε″) values that can be used to characterize food quantitatively. It offers a rapid, easy to use and low cost detection compared to current lab-based method. In this work, the effect of changing the heating time and temperature of the pork and chicken samples towards the dielectrics properties were investigated. All meat samples were mixed in a water and samples were heated (stewing) at different time and different temperature. After subjected to the heating process, the dielectric measurements for all samples were taken using VNA machine. ε′ values of chicken samples decreased with increasing frequency and increased with heating time. The higher ε′ values of 120 min chicken samples means longer time of heating gives higher potential for electrical energy storage in the flesh. The spectra of ε′ and ε′’ are dependent on frequency. On the other hand, different results were seen for pork samples. The significant peak was obtained at 31.19 GHz (ε′) and 32.18 GHz (ε″). Values of ε′ and ε″ of pork are highest at 120 min and lowest at 30 min. The dependency with frequency are similar to chicken samples. At different temperature, the dielectric constant of chicken show increment with the rising in temperature and decrease smoothly (with no significant peak) with the increasing of frequency. Pork exhibits similar trend to chicken whereby ε′ values decrease with increasing of frequency. Similarly a distinct peak like before was observed at 31.19 GHz (ε′) and 32.18 GHz (ε″). The above results indicated that at different temperature and different heating time, dielectric properties changed. Furthermore, only for pork sample, a distinct peak can be seen clearly and this help to further differentiate the samples from one another. These results show promising development in using dielectric properties as potential detection methods.